PENGARUH BIMBINGAN KELOMPOK TEKNIK PROBLEM SOLVING MENINGKATKAN MANAJEMEN WAKTU - Diana Pance Hestiyani; Hadi Pranoto; Mudaim (Counseling Milenial (CM), 2024)
The research and development objective expected in this research is to "Find out the effect of group guidance on problem solving techniques to improve students' time management at SMK Negeri 3 Metro". The type of research used is quantitative research, quantitative data is obtained based on the results of assessment scores from filling out student time management questionnaires that researchers give to students. The results of the research carried out are: 1) The Effect of Problem Solving Technique Group Guidance Services to Improve the Time Management of Class XI TJKT Students at SMK Negeri 3 Metro for the 2022/2023 Academic Year. 2) Improving the time management of Class b) the post test score is 18.7. It can be seen from these results that there is an increase by a difference of 6.1. c) and the results of hypothesis testing also show that the t_count results are greater than the t_table with a significance of 0.05, thus H_0 is rejected and H_1 is accepted. This means that in this research there is an influence of group guidance services using problem solving techniques on improving time management in class XI TJKT students at SMK Negeri 3 Metro.